Fibroepithelial hyperplasia and fibrolipoma in a 4-year-old patient: a rare case report - Torsakul, Pannaros; Rirattanapong, Praphasri; Phimonsri , Ruangkhao (Mahidol Dental Journal, 2024)
Fibroepithelial hyperplasia and fibrolipoma are uncommon benign oral lesions that are seldom reported in children. These lesions are typically asymptomatic and characterized by slow growth. This report discusses the rare occurrence of fibroepithelial hyperplasia and fibrolipoma in the oral cavity of a 4-year-old girl. The patient presented with a complaint of pain while consuming due to slow-growing masses in the gingiva extending from the mandibular left second primary molar to the retromolar, along with another painless slow-growing mass at the mandibular left primary canine. During the clinical examination, a smooth surface, non-tender and firm broad base localized pink fibrous nodules were observed at the buccal area from tooth 75 (mandibular left second primary molar) to the retromolar area, measuring approximately 20x10x4 millimeters in size and at the labial area of tooth 73 (mandibular left primary canine), measuring approximately 6x6x2 millimeters in size. The differential diagnoses for the clinical presentation in both areas included irritation fibroma, peripheral ossifying fibroma, pyogenic granuloma, peripheral giant cell granuloma, gingival fibromatosis as a manifestation of systemic disease, and other benign mesenchymal tumors. A surgical excision was performed, and histopathological analysis confirmed the definitive diagnosis of fibroepithelial hyperplasia and fibrolipoma. A recurrence of the lesions was observed during a follow-up period of 1 year and 4 months. This report emphasizes the importance of identifying these rare benign lesions in pediatric patients for accurate diagnosis and effective management. It also provides valuable insights into the management strategies and recurrence potential for such lesions in young patients, emphasizing the need for ongoing monitoring and intervention to ensure optimal patient outcomes.